Dissociation of spikes, synaptic activity, and activity-dependent increments in rat cerebellar blood flow by tonic synaptic inhibition - Caesar, Kirsten (National Academy of Sciences, 2003)
Functional neuroimaging relies on the robust coupling between neuronal activity, metabolism and cerebral blood flow (CBF) to map the brain, but the physiological basis of the neuroimaging signals is still not well understood. Here we applied a pharmacological approach to separate spiking activity, synaptic activity, and the accompanying changes in CBF in rat cerebellar cortex. We report that tonic synaptic inhibition achieved by topical application of γ-aminobutyric acid type A (GABA(A)) (muscimol) or GABA(B) (baclofen) receptor agonists abolished or reduced spontaneous Purkinje cell spiking activity without affecting basal CBF. The magnitude of CBF responses evoked by climbing fiber stimulation decreased gradually over time after exposure to muscimol, being more pronounced in the superficial than in the deep cortical layers. We provide direct evidence in favor of a laminar-specific regulation of CBF in deep cortical layers, independent of dilatation of surface vessels. With prolonged exposure to muscimol, activity-dependent CBF increments disappeared, despite preserved cerebrovascular reactivity to adenosine and preserved local field potentials (LFP). This dissociation of CBF and LFPs suggests that CBF responses are independent of extracellular synaptic currents that generate LFPs. Our work implies that neuronal and vascular signals evoked by glutamatergic pathways are sensitive to synaptic inhibition, and that local mechanisms independent of transmembrane synaptic currents adjust flow to synaptic activity in distinct cortical layers. Our results provide fundamental insights into the functional regulation of blood flow, showing important interference of GABA(A) receptors in translating excitatory input into blood flow responses.